Fundamentals of Heat and Mass Transfer - Incropera, Frank P. (John Wiley and Sons, 1996)
Chapter 1: introduction; chapter 2: introduction to conduction; chapter 3:one-dimensional, steady-state conduction; chapter4: two-dimensional, steady-state conduction; chapter5: transient; chapter6: introduction to convection; chapter7: external flow; chapter8: internal flow; chapter9: free convection; chapter10: boiling and condensation; chapter11: heat exchangers; chapter12: radiation; chapter13: radiation exchange between surfaces; chapter14: diffusion mass transfer.